2020
DOI: 10.1093/neuonc/noaa196
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of convection-enhanced delivery of IL13RA2 and EPHA2 receptor targeted cytotoxins in dogs with spontaneous intracranial gliomas

Abstract: Background The interleukin 13 receptor alpha 2 (IL13RA2) and ephrin type-A receptor 2 (EPHA2) receptors are attractive therapeutic targets, being expressed in ~90% of canine and human gliomas, and absent in normal brain. Clinical trials using an earlier generation IL-13 based cytotoxin showed encouraging clinical effects in human glioma, but met with technical barriers associated with the convection enhanced delivery (CED) method. In this study, IL-13 mutant and Ephrin-A1 (EFNA1)-based bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 32 publications
0
45
0
Order By: Relevance
“… 59 , 60 , 61 , 62 , 63 Case series with palliative treatment outcome information relating to glioma type or grade are lacking. Canine studies evaluating experimental therapies in >3 intracranial gliomas with detailed information on their type and grade have reported MSTs of 119 days (n = 7), 64 224 days (n = 17), 65 248 days (n = 8), 66 and 257 days (n = 8). 67 However, no comparisons were made between differing types or grades.…”
Section: Discussionmentioning
confidence: 99%
“… 59 , 60 , 61 , 62 , 63 Case series with palliative treatment outcome information relating to glioma type or grade are lacking. Canine studies evaluating experimental therapies in >3 intracranial gliomas with detailed information on their type and grade have reported MSTs of 119 days (n = 7), 64 224 days (n = 17), 65 248 days (n = 8), 66 and 257 days (n = 8). 67 However, no comparisons were made between differing types or grades.…”
Section: Discussionmentioning
confidence: 99%
“…Research for CNS drug delivery focuses on three main approaches [ 3 ]: (1) reformulating existing drugs to cross the BBB by physiological transport mechanisms and drug-delivery approaches such as microspheres and colloidal drug-carriers [ 4 ]; (2) minimally invasive/invasive local delivery methods such as convection-enhanced delivery [ 5 , 6 ] and biodegradable wafers; and (3) disrupting the BBB, where non-localized methods include osmotic BBB disruption (BBBd) [ 7 ], while localized approaches include laser interstitial thermotherapy, MRI-guided focused ultrasound (MRgFUS) [ 8 ] and electroporation (EP) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, radiosensitizing drugs may not easily cross the blood-brain barrier and may possibly exert toxic effects per se when administered systemically. On the other hand, locoregional administration of radiosensitizing drugs (e.g., through convection-enhanced delivery) is of difficult technical implementation and at the moment can be performed in few clinical centers only [104,105]. Inhibiting minimal residual disease progression using low doses of radiation delivered soon after guideline therapies may be an alternative fruitful strategy: in multiple glioma initiating cell-driven animal models that accurately recapitulate the heterogeneity and growth patterns of the patients' tumors, it was recently demonstrated that ultra-hyper-FRT started at early stages of tumor progression resulted in a significant delay in tumor progression and an improvement in animal survival [55].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%